Nonlinear modeling and performance analysis of cracked beam microgyroscopes. (15th December 2020) - Larkin, K.; Ghommem, M.; Hunter, A.; Abdelkefi, A.
Highlights: Investigation of multiple edge cracks on the performance of beam microgyroscopes is conducted. Vibrational characteristics of microgyroscopes with multiple cracks are studied. Differential quadrature method is employed to model the nonlinear responses of cracked gyroscopes. Onset of multiple cracks can significantly affect the sensitivity and performance of microgyroscopes. A potential design approach for broadband microgyroscopes manufactured with cracks can be proposed. Abstract: Cracks constitute a common structural defect in microelectromechanical systems that may arise during manufacturing, mechanical fatigue, or shock loading. Areas weakened by cracks increase the flexibility of the microstructure. Depending on the crack severity, the increased flexibility can cause dramatic changes in the static and dynamic behaviors of electrically actuated MEMS. In this work, a numerical investigation of the depth and location of multiple edge cracks on the performance of beam microgyroscopes is conducted. Applying the Griffith strain energy release theorem for an edge crack, the vibrational characteristics of microgyroscopes with multiple cracks including the static deflection, natural frequencies, and mode shapes are studied analytically. Then, the differential quadrature method is employed to model the nonlinear dynamic behaviors of the cracked gyroscope system. Cracks initiated along the driving or sensing directions of the microgyroscope are found to have differing effects on its nonlinear dynamic response. This numerical study reveals that the onset of severe single cracks or a series of multiple cracks can significantly affect the sensitivity of the microgyroscope to base rotations and therefore leads to a degradation in the performance of the damaged MEMS sensor. This study also shows that a potential design approach for broadband microgyroscope systems manufactured with cracks can be proposed. Graphical abstract: Image, graphical abstract